Pengaruh Gaya Kepemimpinan Terhadap Efektivitas Pengambilan Keputusan - Hendriani, Susi; Rika Yohana Sari; Nurhizrah Gistituati (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2024)
This research aims to investigate the influence of leadership style on the effectiveness of decision making in an organizational context. The focus of this research is to analyze the relationship between various leadership styles, such as authoritarian, democratic, transformational, and transactional, with effective decision making results. The results of the data analysis will be used to understand the extent to which certain leadership styles contribute to the quality of the decisions produced. Various decision-making processes, styles and techniques are explored as potential moderator variables in seeing the influence of effective decision-making on organizational progress. It is hoped that the practical implications of this research finding will provide insight for leaders and business practitioners in developing leadership strategies that support effective decision making. By understanding the impact of leadership style on decision making, this research seeks to contribute to the leadership and management literature, while also providing practical guidance for leaders who desire to increase decision effectiveness within their organizations.